Time-temperature-resolved functional and structural changes of phycocyanin extracted from Arthrospira platensis/Spirulina. (30th June 2020) - Böcker, Lukas; Hostettler, Tom; Diener, Michael; Eder, Severin; Demuth, Teresa; Adamcik, Jozef; Reineke, Kai; Leeb, Elena; Nyström, Laura; Mathys, Alexander
Highlights: Continuous and scalable thermal processing of A. platensis / Spirulina protein. Time-temperature resolved denaturation of purified allophycocyanin and c-phycocyanin. Allophycocyanin trimers denature at lower temperature than c-phycocyanin aggregates. Phycocyanin's optical properties and secondary protein structure alter simultaneously. Difference between thermal and chemical denaturation of phycocyanin. Abstract: Arthrospira platensis, commonly known as Spirulina, gains increasing importance as alternative protein source for food production and biotechnological systems. A promising area is functional high-value algae extracts, rich in phycocyanin, a protein-pigment complex derived from A. platensis . This complex has proven functionality as the only natural blue colorant, fluorescent marker and therapeutic agent. The structure-function relationship is heat sensitive, making thermal processing in its production and its subsequent application a crucial aspect. In continuous high-temperature short-time treatments, it was shown how a purified phycocyanin (mixture of allophycocyanin and c-phycocyanin) disassembled and denatured between 50 and 70 °C. Three characteristic transition temperatures were allocated to specific quaternary aggregates. In contrast to sequential chemical denaturation, phycocyanin's chromophore and protein structure were simultaneously affected by thermal processing. Through a functionality assessment, the findings help optimize the efficiency of raw material usage by defining a processing window, enabling targeted process control resulting in desired product properties.